Analisis sektor unggulan perekonomian Provinsi Jambi - Bambang Novriansyah; Syamsurijal Tan; Rosmeli Rosmeli (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This study identifies the leading sectors in the regional economy of Jambi Province and the share and growth of these top sectors. This study uses secondary data in monographs from the Central Statistics Agency of Jambi Province. The analytical method used is Location Quotient (LQ) and Klassen Typology analysis and use quantitative analysis. Based on the results of the research shows that the leading sectors in Jambi Province are the Agriculture, Forestry and Fisheries sectors, Government Administration, Defense, and Social Security sectors, Construction sector, Real Estate sector, Educational Services sector, Wholesale and Retail Trade sector, Car and Motorcycle Repair, Sector Information and Communication, Health and Insurance Services sector, and Other Services sector. Meanwhile, the fast growth and significant contribution share is the Agriculture, Forestry and Fisheries sector and the Food and Drink Accommodation Provision sector.